KEPEMIMPINAN PARA PEREMPUAN MUSLIM DARI KERAJAAN ACEH DARUSSALAM (1641-1699) - Dedeh Mursyi (IAIN Syekh Nurjati Cirebon, 2017)
History of Acehnese women who fought heroically and patriotic; They are not only willing to fight in the battlefield, but also in political leadership, recorded that Aceh led by sultanah (women leaders) for 59 years. This long history proves that Acehnese women have been self-serving in various fields, both as low-level leaders up to the highest leaders in society. The courage and crookedness of Acehnese women is extraordinary, especially in defending the ideals of nationality and religion. Therefore, Aceh deserves to be called the emancipation pioneer.Keywords: female leadership, the kingdom of Aceh Darussalam